INCREASING ENERGY EFFICIENCY OF TRANSPORT ELECTRIC COOLING SYSTEMS USING MAGNETOCALOR ELEMENTS (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the issues of increasing the energy efficiency of electric cooling systems for vehicles. The disadvantages of traditional vapor-compressor cooling systems are analyzed, and the advantages of cooling technologies based on the magnetocaloric effect as an alternative are highlighted. The principle of operation of magnetocaloric materials, the possibilities of their application in the transport sector, and the impact on energy saving are scientifically substantiated. According to the research results, magnetocaloric cooling systems are environmentally friendly, quiet, and highly efficient.